Coopetition as a Model of Tourism Participation Management in South Lampung Indonesia - HERMAWAN, Dedy; HUTAGALUNG, Simon Sumanjoyo (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
This article discusses the community participation forms in tourism management and review a model that can be a solution. The study conducted by mixed methods which surveyed 100 respondents, also interview, observation and focus group discussions. The results identified that participation tends to emerge in tourism destination areas with the patterns: (1). Society has a readiness to participate which is dominant in the form of thought and energy, (2). Most people are participated if mobilized, there is also a portion which is willing to contribute without waiting to be invited. (3). The public are willing to actively participate but are not in the position of competitors. Model to intervening these conditions is model that adopts the concept of coopetition in the aspect of community empowerment.